PENGARUH LIKUIDITAS, LEVERAGE, PROFITABILITAS DAN SIZE BANK TERHADAP NILAI PERUSAHAAN (Studi Pada Bank Devisa Yang Terdaftar Di Bursa Efek Indonesia) - Priyoko, Dadan; Syaifuddin, Dedy Takdir; Sujono, Sujono (Pascasarjana Universitas Halu Oleo, 2019)
The research aims: 1) analyze the effect of liquidity on firm value, 2) analyze the influence of leverage on firm value, 3) influence profitability on firm value, 4) analyze the influence of firm size on firm value.The object of research is a banking company listed on the Indonesia Stock Exchange. The population in this study are the Foreign Exchange Banks listed on the Indonesia Stock Exchange since 2012 which were announced as 24 banking companies. The sample selection technique uses purposive sampling method, thus the study sample evaluates 16 banking companies with a 5-year observation period so that the data analyzed is collected by 80 observations. The method of collecting data through financial reports published through the IDX website. The data in the study were analyzed by path analysis and using smartPLS 2 software.The results of this study: 1) liquidity has a negative and significant effect on firm value, 2) leverage affects negatively and not significantly on firm value, 3) profitability affects positively and significantly on firm value, 4) firm size affects negatively and significantly on firm value.Â Keywords: liquidity, leverage, profitability and firm value